2022
DOI: 10.3390/tropicalmed7100263
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Relapse, Reinfection and Recrudescence on Malaria Eradication Policy: A Bifurcation and Optimal Control Analysis

Abstract: In the present study, we propose and analyze an epidemic mathematical model for malaria dynamics, considering multiple recurrent phenomena: relapse, reinfection, and recrudescence. A limitation in hospital bed capacity, which can affect the treatment rate, is modeled using a saturated treatment function. The qualitative behavior of the model, covering the existence and stability criteria of the endemic equilibrium, is investigated rigorously. The concept of the basic reproduction number of the proposed model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Acquiring some partial immunity (i.e. some degree of protection against malaria) following infection that wanes over time, is most common among published models [ 56 , 58 – 62 , 64 , 69 , 70 , 79 , 84 ]. Some assumptions regarding immunity include that, if treated, individuals acquire some level of immunity that reduces the probability of reinfection (i.e.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Acquiring some partial immunity (i.e. some degree of protection against malaria) following infection that wanes over time, is most common among published models [ 56 , 58 – 62 , 64 , 69 , 70 , 79 , 84 ]. Some assumptions regarding immunity include that, if treated, individuals acquire some level of immunity that reduces the probability of reinfection (i.e.…”
Section: Search Resultsmentioning
confidence: 99%
“…In most of the models included in this review, it was assumed that treatment would be targeted towards infected individuals [ 21 , 30 , 32 , 64 – 66 , 70 , 79 , 80 , 83 , 85 , 145 ], but a range of other interventions can contribute to malaria control. The impact of a pre-erythrocytic vaccine on reducing P. vivax transmission has been studied and hypothesised that even with low efficacy, it can substantially reduce transmission [ 67 ].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We solve the model in (20) with and without control numerically by applying the backward and forward sweep as described in [45]. Readers who are interested to see further examples on the implementation of this algorithm may refer to [33,[46][47][48]. In the beginning, we give an initial guess for u 1 t and u 2 t constant for all time t. With this initial guess, we solve system (20) forward in time.…”
Section: Optimal Control Problemmentioning
confidence: 99%
“…Recrudescence is the reappearance of parasite forms in the bloodstream after they have been treated to undetectable levels for a period of time, with the presence of plasma concentrations of chloroquine (CQ) and desethylchloroquine (DCQ) higher than 100 ng/mL 11 – 13 . Relapse occurs due to the reactivation of the dormant "hypnozoite" located in the liver 14 . Previous research indicated that relapses account for approximately 90% of P. vivax malaria cases in several countries where the disease is prevalent 15 .…”
Section: Introductionmentioning
confidence: 99%